Perception of tourists from Lima about the Paracas National Reserve in times of Covid-19 (Peru) - Cordova-Buiza, Franklin; Carbajal, Marjorie Riofrio; Fabián, Daniel Amadeo Robles; Benavides, Heber Luis Olavarria (CENTRAL ASIA AND THE CAUCASUS, 2021)
Biodiversity is a significant element in tourist perception of a nature destination. The objective of this study is to analyze the perception of tourists from Lima about the Paracas National Reserve in times of Covid-19. This is a quantitative, descriptive, cross-sectional and non-experimental research work. An online questionnaire was applied to Lima Metropolitan residents who had visited the reserve before and during the pandemic. For data collection, the survey technique with the Google Forms tool was used; the results were tabulated and the quantitative data were analyzed by using the MS Excel tool.The findings show that tourists from Lima value the biodiversity of the Paracas National Reserve more highly during the pandemic, the average stay of 5 days has not changed, and now they are concerned about staying healthy, taking into account the protocols recommended by the state.